(untitled) (Argos, 2024)
The purpose of this article is to analyze the reception of Thucydides’s work in the early stages of the 21st-century within the context of American military intervention in Iraq and the debate over the imperial nature of the United States. The history of a classical Athens and its empire, as it can be noticed, is used to bear upon political debates, where the past is burdened with the task of “legitimation” and “warning”. We conclude that the Athenian Empire formed an alternative model, that can be named hegemony, for those scholars and specialists who are reluctant to compare the United States with the Roman model.